Similar clinical and laboratory findings in patients with symptomatic autosomal dominant and sporadic pseudohypoparathyroidism type Ib despite different epigenetic changes at the GNAS locus - Agnès Linglart; Murat Bastepe; Harald Jüppner (Clinical Endocrinology, 2007)
Summary Objective Most patients with autosomal dominant pseudohypoparathyroidism type Ib (AD‐PHP‐Ib) carry an identical maternally inherited 3‐kb microdeletion up‐stream of GNAS ( STX16 del4‐6 mat ), which is associated with a methylation loss restricted to exon A/B. STX16 del4‐6 mat is not found in sporadic PHP‐Ib (sporPHP‐Ib) patients, who show broad GNAS methylation changes. Because of the epigenetic differences between both groups, we searched for clinical and/or laboratory differences. Patients and methods Age at diagnosis, calcium, phosphorus and PTH were analysed in 43 patients with AD‐PHP‐Ib due to STX16 del4‐6 mat and in 22 patients with sporPHP‐Ib. Results All AD‐PHP‐Ib patients with STX16 del4‐6 mat showed only loss of exon A/B methylation. Of the 43 individuals, 26 were symptomatic when diagnosis was established at age 12·1 ± 1·34 years (mean ± SEM); laboratory findings at presentation were calcium 1·69 ± 0·06 mmol/l, phosphorus 2·25 ± 0·12 mmol/l and PTH 442 ± 54·1 pg/ml. The remaining 17 individuals with STX16 del4‐6 mat were asymptomatic when diagnosed at age 23·5 ± 3·93 years (calcium 2·18 ± 0·05 mmol/l, phosphorus 1·63 ± 0·10 mmol/l, PTH 222 ± 40·3 pg/ml). Patients with sporPHP‐Ib showed methylation changes at two or more GNAS exons, presented at age 10·0 ± 1·01 years and had, as a group, similar laboratory findings as patients with symptomatic AD‐PHP‐Ib (calcium 1·51 ± 0·06 mmol/l, phosphorus 2·65 ± 0·10 mmol/l, PTH 634 ± 162·1 pg/ml). However, sporPHP‐Ib females appeared to be more severely affected. Conclusions Patients with symptomatic AD‐PHP‐Ib due to STX16 del4‐6 mat and sporPHP‐Ib have similar changes in calcium, phosphate and PTH. STX16 del4‐6 mat often leads to asymptomatic disease and screening of all siblings of affected individuals is therefore advised. The cause of the apparent sexual dimorphism in patients with sporPHP‐Ib remains uncertain.